On the Parameters consideration & analysis of menderline antenna for wireless sensor networks - Rajurkar, Harish; Sudhir Akojwar, Dr (International Journal of Engineering and Technology, 2018)
The objective of this paper is to present an analysis of menderline monopole antennas, which are applicable to wireless sensor networks in agricultural. In this paper, a 2.4 GHz Menderline Monopole Antenna (MLMA) is proposed for wireless sensors network. This work presents the detailed analysis of menderline antenna and variation of mender line parameter on antenna performance. A MLMA is modeled at 2.4 GHz with substrate of FR4 with dielectric constant (Îµr) of 4.4. The performance of the MLMA is enhanced by using optimum geometry. The better performance in terms of bandwidth and impedance matching is found. For the proposed MLMA, the bandwidth of 149MHz and return loss of -23.98dB is obtained. The proposed work shows good performance of MLMA, in terms of geometric size, bandwidth and return loss which makes it suitable for wireless sensor network.Â